Chewable Tablet Formulation from Ethanol Extracts of Betel, Areca, and Gambir as a Substitute for Betel - Lestari, Uce; Novra, Ardi; Kurniadi, Romi (Jurnal Jamu Indonesia, 2025)
The tradition of betel nut needs to be preserved because it is useful for maintaining oral health and the digestive system, but this betel nut has an impact on oral cavity injuries. Therefore, to prevent injuries to the oral cavity, this research makes an interesting innovation from the betel nut tradition in the form of formulating safe chewable tablets using natural ingredients, such as betel nut, areca nut, and gambier. This study aimed to determine the best chewable tablet formula from three formulas with different concentrations of betel, areca nut, gambier, and whiting, by testing the physical properties of both granules and formulated tablets. The selection of raw materials begins with the extraction of betel, areca nut, gambier, and whiting by maceration using 70% ethanol solvent and the addition of chewable tablet auxiliaries, such as talcum, magnesium stearate, PVP, aspartame, sorbitol, and aerosol. These chewable tablets are designed to provide the same health benefits as betel nuts, without the risk of tooth damage. The results showed that F2 chewable tablets had the best physical properties of the whole formula, namely weight uniformity with an average of 185±1 mg, average tablet diameter of 9.830±1 mm, average tablet thickness of 2.032±1 mm, and average tablet friability of 1.08±1%. The best formulation F2 contains 10% betel extract, 7% areca nut, 7% gambier, and 4% whiting.